Yield of ‘Superior’ potatoes (Solanum tuberosum) and dynamics of root-lesion nematode (Pratylenchus penetrans) populations following “nematode suppressive” cover crops and fumigation - McKeown, A.W.; Potter, J.W.. (Phytoprotection, 2001)
Studies were conducted at Simcoe, Ontario from 1992 to 1996 to evaluate various cover crop species as possible alternatives to fumigation prior to potatoes (Solanum tuberosum). Cereal rye (Secale cereale), a common overwinter cover crop in vegetable production systems, is an excellent host for the root-lesion nematode (Pratylenchus penetrans) and provides a suitable overwintering host on coarse sandy soils. Vorlex Plus CP and Telone IIB fumigants were compared to 'Domo' mustard (Brassica juncea) for the 1993 and 1994 potato crop years. Rye plus red clover (Trifolium pratense) was included as a known host cover crop system. Cyanogenic plants including 'Domo' mustard (1994) or 'Cutlass' mustard (1995, 1996), 'Forge' canola (Brassica rapa), 'Sordan 79' and 'Trudan 8' sorghum-sudangrass hybrids (Sorghum bicolor), and flax (Linum usitatissimum) were compared to Vorlex Plus CP fumigant and 'NK557' sorghum (Sorghum vulgare) for effects on potato yield and nematodes. Shallow (15 cm) and deep (45 cm) fumigation with Vorlex Plus CP were also compared prior to potatoes for the 1994 to 1996 crop years. There was little detectable difference in percent or days to 50% emergence of potatoes following any treatment. Highest total and marketable yields resulted from Telone IIB fumigation, then Vorlex Plus CP fumigation and 'Domo' mustard, followed by control and rye plus red clover cover. Populations of nematodes surpassed the threshold of 1000 kg-1 soil in all treatments and were highest in potatoes following rye plus red clover. Yield and nematode control following sorghum-sudangrass hybrids and mustards appeared to be intermediate between fumigated and not fumigated. All of the cover crops appeared to be root-lesion nematode hosts in the field, and reduction of population levels appeared to result after incorporation or nematode winterkill. Nematode mortality was excellent with fumigation and next best from kill over the winter after 'Sordan 79' incorporation. 'Sordan 79' grown over at least part of the summer followed by incorporation was an alternative to fumigation prior to potatoes. Deep chiselling appears to reduce nematode population, possibly by physical action. Where nematode populations warrant, deep fumigation prior to potatoes appears to be of merit.